Pharmacological modulation of adrenergic tone alters the vasodilatory response to passive leg movement in young but not in old adults - Fermoyle, Caitlin C.; La Salle, D. Taylor; Alpenglow, Jeremy K.; Craig, Jesse C.; Jarrett, Catherine L.; Broxterman, Ryan M.; McKenzie, Alec I.; Morgan, David E.; Birgenheier, Nathaniel M.; Wray, D. Walter; Richardson, Russell S.; Trinity, Joel D. (Journal of applied physiology (1985), 2023)
Stimulation of α1-adrenergic receptors eliminated age-related differences in passive leg movement (PLM) by decreasing PLM-induced vasodilation in the young. Systemic β-blockade attenuated the central hemodynamic component of the PLM response in young individuals. Inhibition of α-adrenergic receptors did not improve the PLM response in older individuals, though withdrawal of α-adrenergic modulation augmented baseline and maximal vasodilation in both groups. Accordingly, α-adrenergic signaling plays a role in modulating the PLM vasodilatory response in young but not in old adults, and elevated α-adrenergic tone does not appear to contribute to the attenuated vascular function with age identified by PLM. The age-related increase in α-adrenergic tone may contribute to decreased leg vascular conductance (LVC) both at rest and during exercise in the old. However, the effect on passive leg movement (PLM)-induced LVC, a measure of vascular function, which is markedly attenuated in this population, is unknown. Thus, in eight young (25 ± 5 yr) and seven old (65 ± 7 yr) subjects, this investigation examined the impact of systemic β-adrenergic blockade (propanalol, PROP) alone, and PROP combined with either α 1 -adrenergic stimulation (phenylephrine, PE) or α-adrenergic inhibition (phentolamine, PHEN), on PLM-induced vasodilation. LVC, calculated from femoral artery blood flow and pressure, was determined and PLM-induced Δ peak (LVC Δpeak ) and total vasodilation (LVC AUC , area under curve) were documented. PROP decreased LVC Δpeak (PROP: 4.8 ± 1.8, Saline: 7.7 ± 2.7 mL·mmHg −1 , P < 0.001) and LVC AUC (PROP: 1.1 ± 0.7, Saline: 2.4 ± 1.6 mL·mmHg −1 , P = 0.002) in the young, but not in the old (LVC Δpeak , P = 0.931; LVC AUC , P = 0.999). PE reduced baseline LVC (PE: 1.6 ± 0.4, PROP: 2.3 ± 0.4 mL·min −1 ·mmHg −1 , P < 0.01), LVC Δpeak (PE: 3.2 ± 1.3, PROP: 4.8 ± 1.8 mL·min −1 ·mmHg −1 , P = 0.004), and LVC AUC (PE: 0.5 ± 0.4, PROP: 1.1 ± 0.7 mL·mmHg −1 , P = 0.011) in the young, but not in the old (baseline LVC, P = 0.199; LVC Δpeak , P = 0.904; LVC AUC , P = 0.823). PHEN increased LVC at rest and throughout PLM in both groups (drug effect: P < 0.05), however LVC Δpeak was only improved in the young (PHEN: 6.4 ± 3.1, PROP: 4.4 ± 1.5 mL·min −1 ·mmHg −1 , P = 0.004), and not in the old ( P = 0.904). Furthermore, the magnitude of α-adrenergic modulation (PHEN – PE) of LVC Δpeak was greater in the young compared with the old (Young: 3.35 ± 2.32, Old: 0.40 ± 1.59 mL·min −1 ·mmHg −1 , P = 0.019). Therefore, elevated α-adrenergic tone does not appear to contribute to the attenuated vascular function with age identified by PLM. NEW & NOTEWORTHY Stimulation of α1-adrenergic receptors eliminated age-related differences in passive leg movement (PLM) by decreasing PLM-induced vasodilation in the young. Systemic β-blockade attenuated the central hemodynamic component of the PLM response in young individuals. Inhibition of α-adrenergic receptors did not improve the PLM response in older individuals, though withdrawal of α-adrenergic modulation augmented baseline and maximal vasodilation in both groups. Accordingly, α-adrenergic signaling plays a role in modulating the PLM vasodilatory response in young but not in old adults, and elevated α-adrenergic tone does not appear to contribute to the attenuated vascular function with age identified by PLM.